THE INDIVIDUAL FACING THE PANDEMIC - Freitas, Hannah Gomes de; Vasconcelos, Nelson Adriano Ferreira de (Revista JRG de Estudos Acadêmicos, 2021)
This text is an essay in which the authors present their reflections about the pandemic situation caused by the spread of the new coronavirus Sars-CoV-2. The pandemic context has intensified several social issues faced by Brazilian society, a time when psycho-social reflections are necessary to position ourselves as human beings capable of changes and adaptations to the experienced reality. In this perspective, the text in question aims to provoke readers to critically observe the situation experienced from new perspectives, which go beyond the health calamity, as well as reflect on new educational possibilities and dialogues brought by the social isolation scenario.